Audience Reception of Benjamin Master Adhisurya's Self-Image on the TikTok Account @iben_ma - Erlangga Dharma Satria; Vania Utamie Subiakto (Journal of Communication, Sustainability, and Empowerment, 2026)
TikTok social media is one of the social media that can be used to build selfimage. Building a self-image is related to the content on TikTok because someone will exist to create creativity and new things that are different from others. Self-image is a person's image of oneself or a person's thoughts about how others view him or her. The purpose of this study is to determine the reception of Benjamin Master Adhisurya's self-image on the TikTok account @iben_ma. This research uses audience reception theory by referring to Theory 7 of self-image formation to determine the position of the audience in interpreting the content of messages in the media. There are three categories to determine the position of the audience, namely dominant, negotiated, and oppositional. This research uses a qualitative approach using the reception analysis method and uses the constructivism paradigm. The research data collection techniques include primary data with in-depth interviews and secondary data in the form of documentation and literature review. The audience's interpretation of the self-image of TikTok account owner @iben_ma is in a dominant position. The results of this study indicate that most informants accept the meaning of the self-image of @iben_ma in TikTok from various aspects of self-image formation, namely physical condition, name, clothing, social development, family, abilities and knowledge, attitudes and actions. There are four informants who are in a negotiation position accepting the meaning that these factors support @iben_ma's self-image, as well as those who reject the meaning and give meaning based on their views and beliefs, and four informants who are in an oppositional position in the aspects of social development, clothing, attitudes and actions.